Profil Vertikal dan Luas Bidang Dinamika Harian Gradien Suhu Udara di Atas Permukaan Air Danau Tondano di Lokasi Budidaya dan di Luar Lokasi Budidaya Ikan - Andre Dona; Christophil Medellu; Patricia Mardiana Silangen (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
This study aims to determine the temporal and spatial functions of air temperature and the dynamic function of air temperature gradient over the lake surface. This research method was carried out on two transects at the fish farming location and outside the fish farming location. By taking data at nine altitude positions for 24 hours. Measurement time starts from 05:00 am to 05:00 am, with time intervals of 2 hours. Measurement positions according to the vertical distance from the surface of the lake are: 0cm, 10cm, 30cm, 60cm, 100cm, 150cm, 220cm, 300cm, 400cm. Data processing is carried out by compiling the data format in the form of a matrix, then analyzed using an external program or software that includes temporal and spatial functions, functions and the area of ​​the gradient dynamics. The results of this study indicate that mathematical modeling which produces a continuous function of temporal and spatial changes in microclimate variables allows the development of new parameters, namely the dynamics of air temperature gradients. This research was carried out on two different transects with different conditions of the lake ecosystem and its environment. It shows that the area of ​​the plane is formed by the daily dynamic curve of different air temperature gradients for the two transects.